PERSEPSI DAN SIKAP WANITA TANI TERHADAP AGROINDUSTRI PANGAN DI KABUPATEN BANTUL - Supri yati (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2012)
ABSTRACTThe women role in farm activity of agroindustry development is very close with their perception and correlating with motivation of them to create attitude such as cognitive, affective, and conative.Aims of this research were to observe the perception, motivation, and attitude of the women who work in food agroindustry in Bantul Regency.The method of this research was descriptive analytical by applying survey. Sample of area was taken with different level including 4 subdistrictsand4 villages as the main centre of food agroindustryand that was taken 60 households using random, while the analysis method were used in this research were scoring and table analysis. The results showedthat perception of women farmers to process of food agroindustry is positive especiallyon increasing offamily incomeby 61%, sothat result gave them motivation to increase income, basic need, safety by 80,84%. The conclusion of this results was attitude of the women farmers based on cognitive, affective, and conative categories as high more than 90%, this means a good performasnce . It is suggested that government should support them with stimulants and training for improving farmers welfare.Keywords : perception, attitude, motivation, farmers welfare.